THE EFFECTIVENESS OF DRY NEEDLING FOR REDUCING PAIN IN CASES OF HAMSTRING SPASM IN ATHLETES IN PEMATANGSIANTAR - Marolop Parlindungan Napitu; Yeni Trisna Purba; Margaretha Togatorop (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Background: Among the postural muscles, the hamstrings are the ones most prone to tightness at around 68.56%. The prevalence of tight hamstrings is very high, especially among athletes. Objective: Therefore, the aim of this research is to determine the effectiveness of dry needling for reducing pain in cases of gastrocnemius spasm in athletes. Method: This was carried out using PICO searches in several databases such as Google Scholar. There were 5 journals that met the criteria and showed the results that Dry Needling can be applied to Reduce Pain for Hamstring Spasm cases such as with a dry needling size of 0.30 mm*50 mm and a fast in fast out technique. Results: literature using A Quasi-Experimental Study research design, A Double-Blind Randomized Sham- Controlled Pilot Trial, Preliminary Results of a Randomized Within-Participant Clinical Trial, RCT and measurements VAS, NRS with p<0.05. Experimental group using Dry Needling. Conclusion: It can be concluded that Dry Needling is effective in reducing pain in athletes